Research history and alternative interpretations of the Middle/Upper Paleolithic interface in Croatia - Karavanić, Ivor, Smith, Fred (Array, 2011)
A short research history of the Middle/Upper Paleolithic transition in Croatia will be presented. Alternative interpretations of transitional evidence from Vindija and Velika Pecina will be discussed from various perspectives (archaeological, paleoanthropological, genetic). New interpretations are relevant for the debate about Neandertal/early modern human relationships in Central Europe.